2023
DOI: 10.1111/cns.14290
|View full text |Cite
|
Sign up to set email alerts
|

TL1A promotes the postoperative cognitive dysfunction in mice through NLRP3‐mediated A1 differentiation of astrocytes

Abstract: AimWe investigated the mechanism, whereby tumor necrosis factor‐like ligand 1A (TL1A) mediates the A1 differentiation of astrocytes in postoperative cognitive dysfunction (POCD).MethodsThe cognitive and behavioral abilities of mice were assessed by Morris water maze and open field tests, while the levels of key A1 and A2 astrocyte factors were detected by RT‐qPCR. Immunohistochemical (IHC) staining was used to examine the expression of GFAP, western blot was used to assay the levels of related proteins, and en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 23 publications
1
2
0
Order By: Relevance
“…In addition, it has been reported that neuroin ammatory response mediated by the NLRP3 in ammasome was involved in the pathological process of POCD [52]. Using NLPR3-knockout mice and an NLRP3 inhibitor, tissue in ammatory response was signi cantly inhibited, causing amelioration of murine cognitive dysfunction [53]. Our study also supported NLRP3 in ammasome activation in mouse hippocampal microglia after sevo urane exposure, leading to a deterioration in cognitive function.…”
Section: Discussionsupporting
confidence: 79%
“…In addition, it has been reported that neuroin ammatory response mediated by the NLRP3 in ammasome was involved in the pathological process of POCD [52]. Using NLPR3-knockout mice and an NLRP3 inhibitor, tissue in ammatory response was signi cantly inhibited, causing amelioration of murine cognitive dysfunction [53]. Our study also supported NLRP3 in ammasome activation in mouse hippocampal microglia after sevo urane exposure, leading to a deterioration in cognitive function.…”
Section: Discussionsupporting
confidence: 79%
“…In addition, it has been reported that neuroinflammatory response mediated by the NLRP3 inflammasome was involved in the pathological process of POCD 54 . Using NLPR3-knockout mice and an NLRP3 inhibitor, tissue inflammatory response was significantly inhibited, causing amelioration of murine cognitive dysfunction 55 . Our study also supported NLRP3 inflammasome activation in mouse hippocampal microglia after sevoflurane exposure, leading to a deterioration in cognitive function.…”
Section: Discussionmentioning
confidence: 99%
“…Postoperative cognitive dysfunction (POCD) is a type of complication with long-term consequences, defined as impaired memory, attention and information processing that occurs after anesthesia [1]. Studies show that about 10 % of surgery patients as well as 40 % of older patients over the age of 65 develop POCD [2]. Compared to patients without POCD, patients with POCD have significantly higher mortality rates and higher dependence on social security Trop J Pharm Res, November 2023; 22 (11): 2282 [3].…”
Section: Introductionmentioning
confidence: 99%